Assessing individual patients' knowledge of benign versus malignant skin lesions in the dermatology clinic population. Issue 3 (25th July 2022) - Lee, Kristin; Nguyen, Ngoc; Fuzzell, Meghan; Tung-Hahn, Eleanor; Reserva, Jeave; Balasubramanian, Neelam; Tung, Rebecca; Alam, Murad; Stasko, Thomas
Abstract : Background: Skin cancer education targeted to patients' needs is a goal of practicing dermatologists. Data regarding dermatology patients' baseline knowledge regarding skin cancer could aid clinicians in tailoring education efforts. Objective: To help quantify existing patients' existing visual recognition of skin cancer and common benign lesions, with the goal of helping to provide more targeted and meaningful education to patients. Methods: Two hundred forty-four adult patients from the dermatology clinics at University of Oklahoma and Loyola University Chicago were surveyed using digital images and questions regarding personal and family history of skin cancer, sun protection practices and sun protection knowledge. Results: Of the 244 subjects, 43% percent had a positive personal history of skin cancer, 40% had a positive family history. Scores differed minimally by personal history of skin cancer ( p = .37) but differed more markedly by family history of skin cancer ( p = .02). Limitations: Lack of generalizability to the general public, age range of subjects. Conclusions: There are knowledge gaps within the dermatology patient population regarding common benign and malignant skin lesions.